The Effect of Pregnancy Yoga on Discomfort and Anxiety in Facing Childbirth at the JNC Clinic, Metro City - Ike Hesti Puspasari; Dessy Hermawan; Nova Muhani (Viva Medika, 2024)
Pregnancy yoga is one of the measures to facilitate and help anticipate the inevitable changes that come with the arrival of new life to prevent discomfort and anxiety. Anxiety data in the world shows an average of 15.6% of pregnant women experience psychological disorders. In China, 5.3% of pregnant women experience symptoms of depression, 6.8% experience anxiety, 2.4% experience physical discomfort, and in Indonesia, 26.8% experience anxiety before childbirth. The purpose of the study was to determine the average difference before and after doing pregnancy yoga on discomfort and anxiety in facing childbirth in third-trimester pregnant women. This was quantitative research with a pre-experimental pre-test post-test design with one group. The sample consisted of 38 third-trimester pregnant women who were given pregnancy yoga 4 times. The sampling technique used was purposive sampling. Univariate and bivariate dependent t-test data analysis was performed. In conclusion, there is a difference in the average yoga exercise on discomfort and anxiety in third-trimester pregnant women. Advice for pregnant women, pregnancy yoga can be used as a good and safe exercise choice in overcoming discomfort and anxiety.